Reading and librarianship: between concept and practice - Rocha, David Rodrigues (2011)
This work presents, by a descriptive research, the reading practices of the librarianship students from the Brazilian Espírito Santo Federal University (UFES), regularly enrolled in the period of 2009/2. Through a field research, it investigates the relationship of students with book and reading, besides their interest fields and profiles. The research points out that the reading experience involves different processes in its practice and that the librarianship student stereotype, generally so linked to reading and book, not always matches with the reality, since this student demonstrates to keep a functional relationship with the reading along with his undergraduate level.